Quality Information about Uterine Fibroids on the Internet - Melo, Daniela Gama de; Jallad, Pedro Sérgio Soares; Brito, Luiz Gustavo Oliveira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective There are no published studies analyzing the quality of the information for lay women on the Internet regarding uterine fibroids. The accuracy of the provided material is also unknown. Thus, we have performed a cross-sectional study with 381 websites in the English and Brazilian Portuguese languages between May and December 2017.Methods Two investigators performed the analysis, and the Cohen kappa coefficient was calculated to analyze the agreement between them. Search terms (uterine fibroids and derivatives) in the English and Brazilian Portuguese languages were used. The accuracy was analyzed by a 10-item checklist created based on the American Society for Reproductive Medicine (ASRM), National Institutes of Health (NIH) and European Menopause and Andropause Society (EMAS) consensuses about uterine fibroids. The item–test correlation and the intraclass coefficient were performed in the 16 questions from the DISCERN instrument, which was designed to measure the quality of health information on the Internet. Analysis of variance (ANOVA) measurements were performed for the independent variables and the DISCERN/accuracy scores.Results Google was the most used search engine, and uterine fibroid was the search term that generated most of the analyzed material. The median score for accuracy in all websites was 5 out of 10, and the median score of the DISCERN instrument was 38 out of 80. The top-scoring sites in the English language were derived from scientific organizations and federal governments, and they regarded the DISCERN score (The American College of Obstetricians and Gynecologists [ACOG], the Food and Drug Administration [FDA]) and the accuracy criteria (NIH, and FDA). On the other hand, in the Brazilian Portuguese language, the highest scores in both instruments were from magazines or physician's blogs. The Cronbach α test showed a higher correlation (0.77–0.79) between the sites and DISCERN; however, the item–test correlation varied from 0.39 to 0.56.Conclusion There is a need to improve the quality of the information regarding uterine fibroids for lay women.
Keywords: uterine fibroids; quality of information; DISCERN questionnaire; internet